Evidence for Orbital Motion of Material Close to the Central Black Hole of Mrk 766 - Turner, T; Miller, L; George, I; Reeves, J (2005)
Time-resolved X-ray spectroscopy has been obtained for the narrow line Seyfert galaxy Mrk766 from XMM-Newton observations. We present analysis in the energy-time plane of EPIC pn data in the 4-8 keV band with energy resolution R~50. A component of Fe Ka emission detected in the maps shows a variation of photon energy with time that appears both to be statistically significant and to be consistent with sinusoidal variation. We investigate the interpretation that there exists a component of line emission from matter in a Keplerian orbit around a supermassive black hole. The orbit has a period ~165 ks and a line-of-sight velocity ~13,500 km/s. This yields a lower limit for the central mass of M > 4.9x10^5 solar masses within a radius of 3.6 x 10^13 cm (2.4 A.U.). The orbit parameters are consistent with higher black hole masses, but the lack of any substantial gravitational redshift of the orbit implies an upper limit to the black hole mass of 4.5x10^7 solar masses.